Referral and management of patients with melanomas and epitheliomas - Planinšek Ručigaj, Tanja (Onkologija : Slovenian Journal of Oncology, 2013)
The population has become increasingly aware of the importance of health care and knows the risk factors for individual diseases, e.g. the harmful effects of sun rays and their influence on the development of skin cancer, which represents a major problem for a relatively large number of dermato-venereologists dealing with an increasing number of patients. Besides regular examinations, many other patients with an urgent or immediate referral visit the dermato-venereology clinics on a daily basis due to long waiting times, but this only prolongs them.